2003
DOI: 10.1590/s0066-782x2003000200006
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic aspects of spousal concordance for hypertension, obesity, and smoking in a community of Rio de Janeiro, Brazil

Abstract: OBJECTIVE: The present study aims to evaluate the environmental role in the distribution of hypertension, obesity, and smoking and spousal concordance for the presence/absence of these 3 cardiovascular risk factors. METHODS: A cross-sectional study was conducted in a community in Rio de Janeiro, Brazil. The households were randomly selected. Odds ratios were estimated to measure spousal concordance, across socioeconomic levels.. RESULTS: Overall a significant aggregation of all 3 risk factors was present. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…One of the studies was published in Russian, which we translated into English with the assistance of a language translator . The eight studies also differed in study design: one study was a case‐control, five were cross‐sectional, one was a cross‐sectional analysis of baseline data from a prospective cohort, and the last was a cross‐sectional analysis of a cumulative 9‐year longitudinal cohort . Regarding the countries of origin, two studies were conducted in the United Kingdom, two in the United States, two in Russia, one in Brazil and one in China .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the studies was published in Russian, which we translated into English with the assistance of a language translator . The eight studies also differed in study design: one study was a case‐control, five were cross‐sectional, one was a cross‐sectional analysis of baseline data from a prospective cohort, and the last was a cross‐sectional analysis of a cumulative 9‐year longitudinal cohort . Regarding the countries of origin, two studies were conducted in the United Kingdom, two in the United States, two in Russia, one in Brazil and one in China .…”
Section: Resultsmentioning
confidence: 99%
“…The eight studies also differed in study design: one study was a case‐control, five were cross‐sectional, one was a cross‐sectional analysis of baseline data from a prospective cohort, and the last was a cross‐sectional analysis of a cumulative 9‐year longitudinal cohort . Regarding the countries of origin, two studies were conducted in the United Kingdom, two in the United States, two in Russia, one in Brazil and one in China . The outcome was defined as diagnosed hypertension in four studies while as both diagnosed and undiagnosed hypertension in another four studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study that investigated socioeconomic factors and spousal concordance carried out in Brazil, found that non‐smoking concordance increased with higher levels of income and education, but their findings were related to adults aged 20 years and older with a mean age of 43.3 years, and not older adults only 30. The previously mentioned study carried out in Canada found that higher educational levels were associated with increased couple concordance in drinking habits 22.…”
Section: Discussionmentioning
confidence: 95%